THE INFLUENCE OF PROFITABILITY, SOLVENCY AND AUDIT OPINION ON AUDIT DELAY IN COAL SUB-SECTOR COMPANIES LISTED ON THE BEI FOR THE 2018-2020 PERIOD - Siti Helviah Nur Ainun; Arni Karina; Kumba Digdowiseiso (SEAN Institute, 2023)
This research aims to analyze whether profitability, solvency and audit opinion have an effect on audit delay in coal sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The sample population used in this research is coal sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The sampling method used was purposive sampling and a sample of 17 companies was obtained. The data used is secondary data, namely company financial reports and audit reports listed on the Indonesia Stock Exchange in 2018-2020. In order to prove the hypothesis, multiple regression testing was carried out starting with panel data regression. The results of this research show that profitability has a partial effect on audit delay, solvency has no partial effect on audit delay, and audit opinion has no partial effect on audit delay, so it can be concluded that simultaneously the variables solvency and audit opinion have no effect on audit delay. and profitability has a partial effect on audit delay in coal companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2020 period.